A Lewis acidity adjustable organic ammonium cation derived robust protecting shield for stable aqueous zinc-ion batteries by inhibiting the tip effect. (4th March 2022) - Qian, Siyi; Zhou, Jinqiu; Peng, Mingji; Qian, Yijun; Meng, Yuan; Jiang, Yuzhuo; Zeng, Xu; Liu, Jie; Qian, Tao; Yan, Chenglin
Abstract : We explore the effect of organic ammonium cations with different Lewis acidity on the tip effect. Tetraethylammonium cations with medium Lewis acidity can form the most robust protecting shield, thus inhibiting the growth of dendrites. Abstract : Aqueous zinc-ion batteries have attracted extensive attention, but the formation of zinc dendrites has limited their commercialization. Furthermore, on account of the tip effect, Zn cations tend to deposit on top of dendrites, which further exacerbates the growth of dendrites. Herein, we regulate the Lewis acidity of organic ammonium cations to construct the most efficient protecting shield to inhibit the tip effect by adjusting the length of alkyl chains. When selecting tetraethylammonium cations with medium Lewis acidity as the additive, the density functional theory (DFT) calculations confirm that a concentrated positive shielding layer with the largest area could be formed to effectively inhibit the tip effect, and thus uniform Zn electrodeposition could be delivered. Surprisingly, the coulombic efficiency of zinc stripping/plating remained stable at 99.7% after 400 cycles. Moreover, the Zn//LiMnO2 full cell can achieve a high capacity retention of 87.4% after long cycles and maintain an excellent coulombic efficiency of 99.8%.